Midwifery education in Central-Eastern Europe. (February 2016) - Mivšek, Polona; Baškova, Martina; Wilhelmova, Radka
Abstract: Problems in midwifery in many Central-Eastern European countries are very similar; it is possible to speak about the evolving Central-Eastern model of midwifery care. The educational models of this region have a relatively strong theoretical part; however, there is an insufficient practical dimension. Theoretical part of midwifery education in the universities is relatively autonomous and is slowly changing the professional identity of graduates. Highlights: Central-East Europe faces similar situation in midwifery. Midwives in these countries cannot practice in all fields prescribed by EU directives. Theoretical part of midwifery education in the universities is relatively autonomous. Curriculum is slowly changing the professional identity of graduates.